Input-Output Models for Sustainable Industrial Systems Implementation Using LINGO - Tan, Raymond R.; Aviso, Kathleen B.; Promentilla, Michael Angelo B.; Yu, Krista Danielle S.; Santos, Joost R. (Lecture Notes in Management and Industrial Engineering, 2019)
This book addresses the specialized topic of input-output models for sustainable industrial systems. While these models are well-established tools for economic analysis, their underlying mathematical structure is also applicable to the analysis and optimization of a wide range of systems that are characterized by linear interdependencies among their components. This means that input-output models can be used for diverse networks, such as processes within industrial plants, industrial plants in a supply chain, or departmental units within an organization. The models can also be readily extended to interactions between man-made systems and the environment, e.g. flows of natural resources and/or pollutants. Furthermore, model variants with excess degrees of freedom can be formulated to allow optimization and decision-making to be integrated within the framework. This book examines how input-output models can be applied to sustainable industrial systems. Each major variant is discussed separately in a dedicated chapter, and representative case studies and supporting LINGO code are also included.